The Photograph as a Source for the Armenian studies and a Factual Evidence of Documenting History - Tajarian , Yvette (History and Culture, 2025)
Since the invention of photography, specialist from various fields have collaborated with photographers to enhance the depth and clarity of their studies. Each photograph accompanying written texts serves a unique purpose in conveying information. Photographs capturing key moments in Armenian history since the 19th century provide invaluable pictorial evidence, now considered essential sources for Armenian studies and the documentation of historical events. The examples presented in this article demonstrate that, today, photographs play a crucial role in supporting and enriching scientific research, serving as undeniable factual evidence.